Matlab graphical user interface (GUI) code for solar tower power plant performance calculations - Jawad, Ihsan N.; Rishack, Qais A.; Sultan, Hussien S. (Basrah Journal for Engineering Sciences, 2021)
In the present research, a Matlab program with a graphical user interface (GUI) has been established for studying the performance of a solar tower power plant (STPP). The program gives the ability for predicting the performance of STPP for different tower dimensions, ambient operating conditions and locations. The program is based on the solution of a mathematical model derived from the heat and mass balance for the tower components. The GUI program inputs are; tower dimensions, solar radiation, ambient temperature, pressure, wind velocity, turbine efficiency, emissivity and absorptivity for collector and ground and thermal conductivity and thickness for ground. However, the GUI program outputs are; temperature and pressure differences across the collector and tower, velocity in the tower, density of air in collector outlet, mass flowrate of air, efficiency for collector and tower, the overall efficiency and output power of STPP. The effect of the geometrical dimensions of STPP and some climatic variables on the plant performance was also studied. The results show that the output power increases with increasing the collector diameter, chimney diameter and solar radiation by an increasing of 0.282 kW/m, 0.204 kW/m and 0.046 kW/(W/m2) respectively.